Find the value of
1 0 cot ( cot − 1 3 + cot − 1 7 + cot − 1 1 3 + cot − 1 2 1 )
(Source: AIME 1984)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We shall apply the Inverse Trigonometric Identity , cot − 1 x + cot − 1 y = cot − 1 ( x + y x y − 1 ) Note, cot − 1 3 + cot − 1 7 cot − 1 1 3 + cot − 1 2 1 cot − 1 2 + cot − 1 8 = cot − 1 ( 3 + 7 3 ⋅ 7 − 1 ) = cot − 1 2 = cot − 1 ( 1 3 + 2 1 1 3 ⋅ 2 1 − 1 ) = cot − 1 8 = cot − 1 ( 2 + 8 2 ⋅ 8 − 1 ) = cot − 1 2 3 So, we can simplify the given expression as, 1 0 cot ( cot − 1 3 + cot − 1 7 + cot − 1 1 3 + cot − 1 2 1 ) = 1 0 cot [ ( cot − 1 3 + cot − 1 7 ) + ( cot − 1 1 3 + cot − 1 2 1 ) ] = 1 0 cot [ cot − 1 2 + cot − 1 8 ] = 1 0 cot [ cot − 1 2 3 ] = 1 0 ⋅ 2 3 = 1 5
Problem Loading...
Note Loading...
Set Loading...
X = 1 0 cot ( cot − 1 3 + cot − 1 7 + cot − 1 1 3 + cot − 1 2 1 ) = 1 0 cot ( cot − 1 3 + 7 3 ⋅ 7 − 1 + cot − 1 1 3 + 2 1 1 3 ⋅ 2 1 − 1 ) = 1 0 cot ( cot − 1 2 + cot − 1 8 ) = 1 0 cot ( cot − 1 2 + 8 2 ⋅ 8 − 1 ) = 1 0 cot ( cot − 1 2 3 ) = 1 0 ⋅ 2 3 = 1 5